THEORETICAL FOUNDATIONS OF LEISURE ECONOMY - Latipov Ashur Ali; Asadullayev Bakhtiyor (Ecominds Press, 2025)
This article explores the theoretical foundations of the leisure time economy, examining its emergence, stages of development, and its role within modern economic relations. It analyzes the social and economic significance of leisure, particularly its influence on human capital, tourism, culture, sports, and service sectors. The study highlights the correlation between the growth of the leisure economy and factors such as income levels, social infrastructure, and labor productivity. Furthermore, the article reviews international experiences and scholarly sources to assess the prospects of developing a leisure economy within the context of Uzbekistan. The research findings offer practical insights for formulating strategic approaches in this emerging field.
Keywords: Leisure economy, working time, graduate school class, economic development, psychological need, social stratification, Plenitude model, population awareness.